2018
DOI: 10.17925/usor.2018.11.1.56
|View full text |Cite
|
Sign up to set email alerts
|

Keratoconus in a 4-year-old Girl with a Strong Family History of Keratoconus

Abstract: Purpose: To present the diagnosis and management of the youngest-described keratoconus patient, despite the absence of any systemic or local risk factors except the presence of a strongly positive family history of keratoconus. Methods: A retrospective case report. Results: A 4-year-old female child with free past medical and ocular histories, and a strongly positive family history of keratoconus, presented with deterioration in her vision in the previous 6 months as observed by the family. Objective/subjectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Another child had severe eye rubbing, which is also a known risk factor for keratoconus. The third reported case involved a child who also had a strong family history of keratoconus …”
Section: Discussionmentioning
confidence: 99%
“…Another child had severe eye rubbing, which is also a known risk factor for keratoconus. The third reported case involved a child who also had a strong family history of keratoconus …”
Section: Discussionmentioning
confidence: 99%
“…Several reasons might explain the discrepancy in DS patients and KC's prevalence, including the clinical equipment utilized, ethnicity, the lack of cooperation from patients during screening, the diagnostic criteria for KC, sample size, and the patient's age during clinical examinations (<18 years) [30,42,59,60]. It is well known that KC manifests itself throughout the adolescent years, although some are reported to have an onset <10 years old [5,[61][62][63][64]. In a study by Alio et al, the authors noted that approximately 75% of 112 DS patients, comprising 59% Caucasians and 41% Arabs, demonstrated corneal features likely to be characteristic of KC [30].…”
Section: Ophthalmic Manifestations Of Down Syndromementioning
confidence: 99%
“…5,6 Literature reports KCN occurring in patients as young as 4 years old. 7,8 Current estimates for the incidence of KCN in all age groups are 1 in 2000 for the United States. 2 Some studies report KCN incidence as high as 1 in 200 in the pediatric population, representing 2.9% of KCN in all ages.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on KCN have reported the average age of onset to be around puberty, with the diagnosis in young children considered relatively rare 5,6. Literature reports KCN occurring in patients as young as 4 years old 7,8. Current estimates for the incidence of KCN in all age groups are 1 in 2000 for the United States 2.…”
Section: Introductionmentioning
confidence: 99%